From the Suffering of Old Age to the Fullness of Senectitude, a Philosophical Approach - Lázaro Pulido, Manuel; Cintado Fernandez, Purificacion (Philosophia, 2022)
Talking about 'suffering' in relation to 'old age' implies reflecting on its semantic fields, its various references and the relationship between the two in a dynamic way. We therefore propose to reflect first of all, in a philosophical way, on (1) 'suffering' and its specificity in relation to other terms such as 'pain'; (2) then we will look at the meaning of 'old age' and its semantic field: 'old age', 'third age', 'senectitude'; we will continue (3) with the question of the relationship between suffering and elderly people to detect if there is a determination and connection between both realities; to, finally, (4) propose, in continuity with our conclusions, a practical look from the human activity in a humanistic paradigm of Occupational Therapy.
Keywords: old age; senectitute; pain; suffering; elderly people; WOS; Scopus